TELAAH PEMIKIRAN IBN TAYMÃ®YAH TENTANG ARABISASI LINGUISTIK DALAM ALQURAN DAN HADIS - Faruq, Umar (Program Studi Perbandingan Agama, Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri (UIN) Sunan Ampel Surabaya, 2017)
This research is aimed to explore the idea of Arabization in Qur?ân and hadîth and to elaborate the Arabs? innovation who unified their empire around a single faith of Islam and a single language of Arabic. The Arabic language has quickly replaced the earlier cultural languages such as Latin, Greek, Syriac, and Persian. This Arabization impressed that the Arabs were not interested in other languages. For Arabs, to learn an ?infidel? script would involve an element of, so to speak, impiety, even of pollution. This article would explain the idea of Arabization from the view of Ibn Taymîyah, a strict scholar living in the middle time of Islam. He has put Arabic language not only as the medium of communication between God and Human, but he seems to purify the Arabic language as the ultimate language of Muslim world